2016
DOI: 10.1038/ajg.2015.440
|View full text |Cite
|
Sign up to set email alerts
|

The Secondary Quality Indicator to Improve Prediction of Adenoma Miss Rate Apart from Adenoma Detection Rate

Abstract: Among high-ADR endoscopists, AMRs still varied. APP may be a promising secondary indicator for distinguishing between the one-and-done polyp endoscopist and the meticulous endoscopist. The evaluation of influence of new metrics on colorectal cancer (CRC) prevention requires a larger population-based study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 36 publications
5
78
1
1
Order By: Relevance
“…14,15 MAP+ has also been reported to be inversely correlated with adenoma miss rate. 16 These adenoma metrics were valuable targets for colonoscopy quality intervention, and the impact of insertion polypectomy on these secondary quality indicators has not been reported in previous studies. In our study, we found that there was no statistically significant difference of overall ADR and these secondary quality indicators between the two study groups.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…14,15 MAP+ has also been reported to be inversely correlated with adenoma miss rate. 16 These adenoma metrics were valuable targets for colonoscopy quality intervention, and the impact of insertion polypectomy on these secondary quality indicators has not been reported in previous studies. In our study, we found that there was no statistically significant difference of overall ADR and these secondary quality indicators between the two study groups.…”
Section: Discussionmentioning
confidence: 91%
“…MAP, MAP+, and ADR‐Plus have been suggested to supplement the ADR in assessing and comparing the ability of endoscopists in detecting multiple adenomas . MAP+ has also been reported to be inversely correlated with adenoma miss rate . These adenoma metrics were valuable targets for colonoscopy quality intervention, and the impact of insertion polypectomy on these secondary quality indicators has not been reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modified ADR metrics, such as APP (adenoma per positive participant), ADR-plus, polypectomy rate, proximal ADR, AADR (advanced adenoma detection rate), or SSADR (sessile serrated adenoma/polyp detection rate), are now being explored. [64][65][66][67][68][69] It is also important to know that the ADR in a FIT-based screening program is expected to be higher than that for colonoscopy-based screening. 70 LGI consensus statement by ANBI 2 G 233…”
Section: Statement 3-1: Image-enhanced Endoscopy (Iee) Can Improve Pomentioning
confidence: 99%
“…Tandem studies demonstrate differences in additional adenoma detection and report AMR, whereas parallel studies assess simple detection and report ADR. The relationship between ADR and AMR is unclear; a recent trial from Thailand of 200 patients undergoing back-to-back colonoscopies found no correlation between AMR and ADR among high-ADR providers (r=−0.25; p=0.75) 4. Further studies elucidating the difference between the two research approaches are needed.…”
mentioning
confidence: 99%